Model Pendidikan Yang Diberikan Oleh Guru pada Anak Autis di SLB Negeri I Palangka Raya - Dwi Sari Usop (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2014)
Children with autism are children with distinctive characteristics that require unique education anyway. Therefore, teachers understanding to the characteristics of children with autism are very helpful in the selection of a given model of education. This research was conducted in SLBN 1 Palangkaraya in order to determine the characteristics of children with autism in SLBN 1 Palangka Raya as well as a model of education provided by the teachers. The study focused on children with autism in Junior High School, amounting to 5 (five) people. Based on the results of the study, there were differences in the characteristics possessed by the five children with autism. Such differences can be observed from the ability to speak and the ability of the learning process. While based on the edsucational model used by the teacher is a model of behavior modification. Through this model of behavior modification, children with autism are educated to have the ability to interact socially and communicate with others and able to be part of the class.